E-learning experience during COVID-19 pandemic management:Perception of secondary schools teachers' in Morocco - Hajar El Omari; Khadija Chlouchi; Fatima Zahra Talbi; Moussa Benboubker; Meryem Mrani Alaoui; Khadija Lahouiti; Amina Chlouchi; Saad Maniar; Abdelilah Merabti; Abdelkarim Taam; Abdelhakim El Ouali Lalami (Scientific African, 2023)
Around the world, the COVID-19 pandemic quickly led to the closure of educational institutions in the hope of reducing infections and fatalities due to this disease. Distant education is becoming a policy priority, although institutions and teachers are neither experienced nor accustomed to its use.The purpose of this study is to determine secondary school teachers' perceptions and requirements of distance education during confinement. To our knowledge, none of the similar studies conducted in this area has approached this issue in Morocco. To determine teachers' perceptions regarding distance education, we conducted an analytical and descriptive survey among secondary school teachers in May, June, and July 2020.The chi-square test has been used to test the association between all variables. The association was considered significant when the p-value < 0.05. The calculation of the chi² (X²) and the p-value is performed using R software.The grouping of responses show that most teachers have been teaching remotely during confinement using Whatsapp. They confirmed that this is a useful way to ensure pedagogical continuity during the break from classroom teaching, and they also indicated a preference for both face-to-face and hybrid tutoring.Statistical analysis showed a significant correlation between the subjects taught and distance education (X2= 67.4 with p = 0.01), and a low correlation between training follow-up and distance education during the confinement period r = 0.12.This national study, focused in the secondary school teachers, is pertinent and has showen the extent of the problems of continuous teacher training, as well as strategies that are not evaluated and which do not take into account the perceptions of the actors, including the teacher. This data will be valuable and can be used to establish appropriate measures for improving distance learning tools and the quality and competencies of the actors.